The Egyptian Organization for Standardization and Quality Administrative Resolution No. 94 of the Year 2014 With Regard to Announcing in Al-Wakaye Al-Mesreya / Government Bulletin the Amendments Related to A Set of Egyptian Standard Specifications Concerning Which Binding Ministerial Decrees Were Previously Issued = الهيئة المصرية العامة للمواصفات والجودة قرار إدارى رقم 94 لسنة 2014 بشأن الإعلان بجريدة الوقائع المصرية عن تعديلات على مواصفات قياسية مصرية سبق صدور قرارات وزارية ملزمة لها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic